-24x+9x=3(-11-6x)

Simple and best practice solution for -24x+9x=3(-11-6x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -24x+9x=3(-11-6x) equation:



-24x+9x=3(-11-6x)
We move all terms to the left:
-24x+9x-(3(-11-6x))=0
We add all the numbers together, and all the variables
-24x+9x-(3(-6x-11))=0
We add all the numbers together, and all the variables
-15x-(3(-6x-11))=0
We calculate terms in parentheses: -(3(-6x-11)), so:
3(-6x-11)
We multiply parentheses
-18x-33
Back to the equation:
-(-18x-33)
We get rid of parentheses
-15x+18x+33=0
We add all the numbers together, and all the variables
3x+33=0
We move all terms containing x to the left, all other terms to the right
3x=-33
x=-33/3
x=-11

See similar equations:

| 25x+27=26x+36 | | 3/4s-3/4=s/8+3/4 | | -2b+13=9b+7 | | 100=0.25d^2 | | x+15=64 | | 1200=66(r) | | 5y-14=-3y+18 | | 6(-x)=30-5x | | -12=d/4+8 | | 5-5+(-6)=x | | -3x+4=-12 | | -18=4p+2 | | 2t—4;t=6 | | 28=x*3x | | 3x1=72/12-5 | | 3x1=72/9-5 | | 3x1=72/8-5 | | g/21=66 | | 3x1=72/6-5 | | 12;n=3 | | 6=18x/360 | | 6(v-5)=4v-10 | | 3x-x+2x=3x+1 | | 5w+10=60 | | -5v+40=2(v+6) | | 8x-56=x+28 | | 2(v+8)=-5v-47 | | -15,-4m=1/2 | | 9,-10m=-4 | | 3g−1=7g+1 | | 1/2x-0,3=1/4x+0,7 | | -7,8m=-3 |

Equations solver categories